Limitations of Quantitative Methods for Research on Values in Sexuality Education - Morris, Ronald (Canadian Journal of Education/Revue canadienne de l’éducation, 1991)
Quantitative methods are rarely appropriate for research on values in sexuality education. Survey research cannot capture the richness, complexity, and depth of value questions. It pays no attention to levels of meaning, nuances in language, or lived values. Experimental research abstracts values, valuing, and sexuality education from their social, institutional, and relational contexts. Experimental designs are also undergirded by epistemological assumptions that are difficult to reconcile with research on values. Les méthodes quantitatives sont rarement utiles pour mener à bien des recherches sur les valeurs dans le domaine de l'éducation sexuelle. Les sondages ne peuvent capter la richesse, la complexité et la profondeur des questions ayant trait aux valeurs. Ils ne tiennent pas compte des niveaux de signification, des nuances de langage ou des valeurs vécues. La recherche expérimentale extrait les valeurs, les jugements de valeur et l'éducation sexuelle de leurs contextes sociaux, institu- tionnels ou relationnels. Elle repose en outre sur des hypothèses épistémologiques qu'il est difficile de concilier avec une recherche axée sur des valeurs.